Identifikasi Colletotrichum spp. Asal Tanaman Pepaya - Eryna Elfasari Rangkuti; Suryo Wiyono; Widodo Widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Colletotrichum spp. is known as the causal agent of anthracnose and considered as an important limiting factors on papaya production. The objective of this study was to determine the species of Colletotrichum spp. from various plant parts of papaya (Carica papaya) showing anthracnose symptom. Twenty isolates of Colletotrichum spp. was isolated and were grouped into 3 morphological groups based on colony similarity, conidial morphology, and setae formation. A total of 12 isolates of group I and 3 isolates of group II were identified morphologically as C. gloeosporioides sensu lato based on cylindrical conidia with rounded on both ends and colony morphology. Meanwhile, 1 isolate of group II was molecularly identified as C. magnum. Four isolates of group III with a curved and pointed-end conidia, and produced setae on artificial medium were identified molecularly as C. truncatum. C. gloeosporioides was obtained on stem, leaf petiole, and fruit. C. magnum and C. truncatum were only obtained on leaf petiole and fruit, respectively. In addition to morphological and molecular characters, differences in colony growth responses to temperature can be used to distinguish the species of Colletotrichum. To our knowledge the existence of anthracnose symptom on the stems and leaf petioles of papaya in the fields and the discovery of C. magnum and C. truncatum isolated from papaya was the first report in Indonesia.